A retroperitoneal cavernous hemangioma arising from the gonadal vein: A case report. Issue 38 (18th September 2020) - Laih, Chun-Yo; Hsieh, Po-Fan; Chen, Guang-Heng; Chang, Han; Lin, Wei-Ching; Lai, Chun-Ming; Chang, Chao-Hsiang
Abstract: Rationale: Cavernous hemangioma (CH) is not commonly found within the abdomen or the retroperitoneum. We report the first case of CH originating from the gonadal vein. Diagnosis: A retroperitoneal tumor was found incidentally in a 57-year-old female patient. The differential diagnoses from the initial imaging studies included gastrointestinal stromal tumor, carcinoid tumor, neurogenic tumor, metastasis, lymphadenopathy, or another rare tumor. Interventions: A surgical en-bloc excision was performed via a subcostal incision and intravenous CH arising from a gonadal vein was diagnosis by the urological pathologist. Outcomes: After the surgery, no complications were noted. A computed tomography scan was performed after 3 months follow-up and no tumor recurrence was found. Lessons: This case reminds us that CH should be listed as one of the differential diagnoses for a retroperitoneal tumor. A definite diagnosis of CH relies on surgical resection. The prognosis is well if adequate resection is performed.